OPERATORS OF GENERALIZED DERIVATIONS ON NUMERICAL METHODS FOR SOLVING NONLINEAR TRANSFER EQUATION WITH APPROXIMATE DATA - Roman Andreevich Ryskalenko; Mariya Sergeevna Chemerigina (Вестник Северо-Кавказского федерального университета)
The work considers the nonlinear mathematical model of substance transfer in a turbulent atmosphere, which involves the use of empirical data. Construction of the corresponding recursive algorithm is performed on the basis of a generalized derivation.